Effects of Group Counseling Based on Logo Therapy to Decrease Loneliness in Elderly Men - Negin Yazdanbakhsh; Seyed Jalal Younesi; Soraya Aazimiyan; Mahshid Foroughan (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives The elderly are an increasing social group in the present society which has gained importance in the age pyramid of our country. The present study aimed to examine the effects of group counseling based on "logo-therapy" as a method of rehabilitation to reduce loneliness in elderly men. Methods & Materials This was a quasi-experimental study with pretest posttest and control group. Thirty-six elderly men from Jahandidegan center in Tehran were selected for our study by sampling. They were randomly divided into two groups; experimental and control. Each group consisted of 18 men. Group logo therapy was applied to the experimental group for eight 90-minute sessions, once a week. Follow-up test was conducted one month after the test. We used the Dehshiri et al. Loneliness questionnaire (2008) to assess the level of loneliness. Results Using analysis of covariance, our findings showed that group counseling based on logo therapy had meaningful and positive effect on decreasing loneliness of elderly male in the experimental groups (P<0.003).    Conclusion Group counseling based on logo therapy was found to decrease loneliness scores of elderly men. Therefore, the approach taken in this study can be considered as an appropriate method for psychological interventions in elderly men.